PERANAN ORANG TUA TERHADAP PENDIDIKAN ANAK DI DESA NAKUPIA KECAMATAN TNS - Telussa, Rivaldo Paul; Huliselan, Reky Hiskia; Telussa, Nova (PEDAGOGIKA: Jurnal Pedagogik dan Dinamika Pendidikan, 2024)
This study aims to determine the role of parents towards children's education in Nakupia Village, TNS District. This research uses qualitative research methods with case study research type. The research data were collected using interview, observation, and documentation techniques with research subjects consisting of 10 parents who have school-age children in the village. The research data were analyzed using an interactive analysis model. The results found that the role of people towards children's education in Nakupia village, TNS sub-district includes: parents' understanding of the importance of education for children, parent's attitudes towards children's education, parent's actions towards children's education. Factors that influence the role of parent's towards children's education are internal factors including education level, occupation, income, knowledge, skills, attitudes, values and parental beliefs. And external factors which include environment, culture, social, economic, political, and legal. Based on the results of this study, it can be concluded that parents have a very important role in children's education so that it can have a positive impact.